Chemical analyses of ferromanganese oxide crusts from the Indian Ocean - N M Colley; David S Cronan; S A Moorby (PANGAEA, 2022)
A suite of ferromanganese oxide crust specimens was collected by R.R.S. Shackleton in 1975 as part of the continuing study at Imperial College of North West Indian Ocean nodules and encrustations. The samples analysed were drilled out at points of varying depth within the specimens using a hand drill with a 2 mm stainless steel bit. The samples were then ground up and dried in a desiccator. They were subjected to a standard HF/HNO3/HClO4 attack, and taken into solution for analysis by atomic absorption spectrophotometry for Fe, M n, Co, Pb, Cu, Zn, Al, Ti, Mg, Ca, Cd and Li. Analytical precisions were generally better than 10 96, and usually better than 5 %. However, Cd and Li had precisions generally worse than 15 % , because their concentrations were nearer the detection limit of the method.